Practical recommendations for diagnosis, management, and follow-up of Niemann-Pick type-C disease patients: a Brazilian perspective - Dafne Dain Gandelman Horovitz; André Pessoa; Marcondes Cavalcante França Junior; Roberto Giugliani; Carolina Fischinger Moura de Souza; Emília Katiane Embiruçu; Pedro Braga-Neto; Charles Marques Lourenço (Arquivos de Neuro-Psiquiatria)
Niemann-Pick type-C (NPC) disease is a rare genetic condition with a clinical spectrum ranging from a fatal prenatally-presenting and quickly lethal disorder to an adult-onset chronic neurodegenerative condition. Given the scarcity of information regarding NPC disease in Brazil, a group of experts decided to discuss some disease-related aspects at the national level. The present manuscript describes the results of a Brazilian consensus meeting conducted to propose recommendations for the diagnosis, management, and follow-up of NPC disease in Brazil, considering the clinical practice point of view. These recommendations include patient characteristics on clinical presentation, as systemic and neurological manifestations according to the age group and atypical manifestations; a flowchart for diagnostic confirmation, considering the Brazilian scenario; and treatment, encompassing disease-modifying therapy, supportive care, and patients' follow-up. The expert panel provided an objective basis of recommendations on NPC diagnosis and management in Brazil. The authors expect that this manuscript will help clinicians to identify, adequately treat and follow-up NPC patients in Brazil.